Association of malnutrition-inflammation complex and responsiveness to erythropoiesis stimulating agents in hemodialysis patients - Manoch Rattanasompattikul; Miklos Z Molnar; Joshua J Zaritsky; Parta Hatamizadeh; Jennie Jing; Keith C Norris; Csaba P Kovesdy; Kamyar Kalantar-Zadeh (The Korean Society of Nephrology, 2012)
Protein-energy wasting, inflammation and refractory anemia are common in long-term hemodialysis patients. A decreased responsiveness to erythropoiesis stimulating agents (ESA) is often the cause of the refractory anemia. A 6-year prospective cohort study of 754 hemodialysis patients, we hypothesized that malnutrition-inflammation score (MIS) is an independent predictor of decreased responsiveness to ESAs (ERI) in hemodialysis patients. Mean age of patients was 54±15 years, 53% were diabetic and 49% Hispanic. A positive correlation was found between ERI and inflammatory markers including C-reactive protein (CRP) (r=0.16) and interleukin-6 (IL-6) (r=0.16). We also found negative correlations between ERI and serum albumin (r=−0.22). Each 5 unit higher MIS, 1 mg/L higher CRP and 0.5 g/dl lower albumin were associated with 46%, 45% and 140% higher likelihood of highest vs. lowest ERI in fully adjusted logistic regression models (odds ratio [and 95% CI] of 1.46 [1.05-2.05], 1.45 [1.06-1.98], and 2.40 [1.54-3.74]) respectively. Cubic splines illustrated continuous and incremental nature of MIS and ERI associations (Figure). Malnutrition-inflammation complex is a significant and independent predictor of decreased responsiveness to ESAs in hemodialysis patients. fx1